Rac1-regulated endothelial radiation response stimulates extravasation and metastasis that can be blocked by HMG-CoA reductase inhibitors. - Melanie Hamalukic (Public Library of Science (PLoS), 2011)
Radiotherapy (RT) plays a key role in cancer treatment. Although the benefit of ionizing radiation (IR) is well established, some findings raise the possibility that irradiation of the primary tumor not only triggers a killing response but also increases the metastatic potential of surviving tumor cells. Here we addressed the question of whether irradiation of normal cells outside of the primary tumor augments metastasis by stimulating the extravasation of circulating tumor cells. We show that IR exposure of human endothelial cells (EC), tumor cells (TC) or both increases TC-EC adhesion in vitro. IR-stimulated TC-EC adhesion was blocked by the HMG-CoA reductase inhibitor lovastatin. Glycyrrhizic acid from liquorice root, which acts as a Sialyl-Lewis X mimetic drug, and the Rac1 inhibitor NSC23766 also reduced TC-EC adhesion. To examine the in vivo relevance of these findings, tumorigenic cells were injected into the tail vein of immunodeficient mice followed by total body irradiation (TBI). The data obtained show that TBI dramatically enhances tumor cell extravasation and lung metastasis. This pro-metastatic radiation effect was blocked by pre-treating mice with lovastatin, glycyrrhizic acid or NSC23766. TBI of mice prior to tumor cell transplantation also stimulated metastasis, which was again blocked by lovastatin. The data point to a pro-metastatic trans-effect of RT, which likely rests on the endothelial radiation response promoting the extravasation of circulating tumor cells. Administration of the widely used lipid-lowering drug lovastatin prior to irradiation counteracts this process, likely by suppressing Rac1-regulated E-selectin expression following irradiation. The data support the concern that radiation exposure might increase the extravasation of circulating tumor cells and recommend co-administration of lipid-lowering drugs to avoid this adverse effect of ionizing radiation.